Dami kaniat . Lady's Choice - Andonov, Ivan (Sredets at Boyana Film Studio, 1980)
Duration: 01:35:00 Donev the driving instructor is both divorced and poor, and nice and charming. He enjoys women’s affection and in his turn, does his best not to disappoint them. Every day is marked by new adventures, ups and downs. The life of this country Don Juan is movable feast until the moment when he loses control over the attacks of his female suitors. The film is a true comedy of relations between the driving-teacher and the beginner-drivers.